Evaluation of Fungicides, Botanicals and Biocontrol Agents for Management of Southern Leaf Blight of Maize (Bipolaris maydis) with Effective Benefit Cost Ratio - Vanlalhruaia; Mahapatra, Sunita; Das, Srikanta (International Journal of Bio-resource and Stress Management, 2022)
Southern leaf blight of maize (Bipolaris maydis) is one of the major disease in many countries including India. An experiment was conducted for two consecutive years during rabi 2019 and 2020 to develop an integrated management of southern leaf blight of maize using fungicides, botanicals and bioagents under natural field conditions. Propiconazole was found to be the best and showed 100% mycelial growth inhibition in vitro at 0.1%. Among the botanicals, citronella showed 99.70% mycelial growth inhibition and Trichoderma harzianum was found to be the bestwith 84.26% mycelial growth inhibition among the biocontrol agents. The results of the field trials showed the highest yield performance (2601.71 kg ha-1) and percent reduction in disease severity over control of 61.70 % in the treatment comprising of seed treatment+spraying with propiconazole 25% EC @ 1% which was followed by treatment comprised of spraying with citronella @ 0.1% (2445.33 kg ha-1) and spraying with propiconazole 25% EC @ 0.1% (2349.26 kg ha-1). Highest BC ratio was obtained in seed treatment+spraying with propiconazole 25% EC @ 1% (4.05) followed by spraying with Trichoderma harzianum @ 4 g (3.71) and seed treatment+spraying with Trichoderma harzianum @ 4 g (3.69). The results showed that seed treatment+spraying with propiconazole 25% EC @ 1% was significantly superior over other treatments.